WORLD OUTLOOK AND WORSHIP OF ANCIENT TURKS (Journal of Oriental Studies, 2018)
The study of the beliefs of ancient Turks and their systematization has historical importance for future generation. Modern historians have come to the conclusion that to study the history of Kazakhstan, it is necessary to know the history of Turks. In the ancient Turkic society’s traditional world outlook the specially describable natural territory was considered sacred and was under protection. There were performanced ceremonial rites in such places in honor of the Creator of the Universe-Lord in the Highest, Umai Ana, the elements of Earth and Water. Here the descendants followed their ancestors to their graves and put up monuments. By ornamenting the figures and placing them in wide steppe the Turkic people placed special importance on the said territories and honored as sacred lands. This way, the ancient open-air sculptures, monuments have become a source of the ancient rituals and traditions for the today’s scientists.